Proxy Users Enable Older People Creative Writing on the Web - Toczyski, Piotr; Kowalski, Jarosław; Biele, Cezary (Frontiers in Sociology, 2019)
This paper presents several state-of-the-art concepts within Internet studies and applies them to the creative writing of older people using the Internet. For more than 10 years two creative Web users aged 80+, assisted by younger proxy users, were involved in preliminary action research. It was aimed at finding patterns of inducing older people's creativity and sharing their wisdom with the general Internet audience. The effectiveness of conducted action research in transferring wisdom using silver digital content is high. It is demonstrated with (a) qualitative participants' insights, (b) the quantitative description of statistics of blog visits, and (c) the social significance of the topics covered in the created content. Lasting for more than a decade and located within the space of socio-technological solutions in Central and Eastern Europe, the results delivered patterns of emerging technologies aimed at enhancing older people's creativity on the Web. The insights from those two action-based case studies enabled the development of new hypotheses. New directions of further, more advanced research of older users' activity are based on interdisciplinary studies at the crossroads of public health, sociological theory, gerontology, and human-computer interaction studies. New research questions are presented, to be explored within the social scientific studies of the next-generation Internet. Departing from the established concepts and preliminary research, the authors hypothesize that: (1) in order to optimize non-human technology-based assistants, human proxy users should be researched; (2) voice assistant technology could become the primary proxy for a production of silver digital content; and (3) interactive and intelligent technology will be the substitute for social actors that prevent exclusion and disengagement. The remaining research question also refers to the conditions under which the technology can be a viable substitute for proxy users.